2014
DOI: 10.4088/jcp.13m08797
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patient Expectancy in Placebo and Nocebo Effects in Antidepressant Trials

Abstract: Objective To determine whether patient expectancy plays a role in observed placebo and nocebo effects in two clinical trials. Method Data were re-analyzed from two fluoxetine-discontinuation studies conducted from March 1990–September 1992 and May 1997–December 2002. Outpatients aged 18–65 years with DSM-III-R Major Depressive Disorder (MDD) responding to 12-week duration open treatment were randomized to continued fluoxetine or placebo for an additional year. Participants in one of the included studies rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 29 publications
4
24
0
1
Order By: Relevance
“…Nocebo has been studied in RCTs for several neurological conditions, including multiple sclerosis [9], headache [10,11], neuropathic pain [12], fibromyalgia [1], diabetic peripheral neuropathy [13], Parkinson's disease [14] and depression [2,15]. In these studies dropouts because of AEs in placebo treated patients varied from 2% (in multiple sclerosis) to almost 10% (in Parksinson's disease and fibromyalgia).…”
Section: Introductionmentioning
confidence: 99%
“…Nocebo has been studied in RCTs for several neurological conditions, including multiple sclerosis [9], headache [10,11], neuropathic pain [12], fibromyalgia [1], diabetic peripheral neuropathy [13], Parkinson's disease [14] and depression [2,15]. In these studies dropouts because of AEs in placebo treated patients varied from 2% (in multiple sclerosis) to almost 10% (in Parksinson's disease and fibromyalgia).…”
Section: Introductionmentioning
confidence: 99%
“…Developing methods of predicting placebo response in youth with MDD could aid efforts to minimize such placebo response in clinical trials as well as aid in targeting such youth in clinical practice with treatment strategy designed to bolster treatment outcome (Rutherford et al, 2014;Trivedi and Rush, 1994). The high placebo response rate (about 59%) in the recent adolescent selegiline transdermal patch randomized controlled trial (RCT) (DelBello et al, 2014), provides some of the necessary foundation for the current study to develop such a method of prediction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that increases and decreases in depressed symptoms immediately after treatment changes are related to patient expectations. Among adults, patients who continued to take antidepressant medications as well as those who were switched to placebos had higher mean depression rating scale scores (47). However, more highly motivated patients showed greater responses to placebos as compared with less motivated patients, which highlights the importance of the patient's own level of motivation (48).…”
Section: Discussionmentioning
confidence: 98%